2007
DOI: 10.1007/s00270-007-9229-9
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Directed Thrombolysis of Inferior Vena Cava Thrombosis in a 13-Day-Old Neonate and Review of Literature

Abstract: Complete inferior vena cava thrombosis (IVC) in neonates is uncommon, but may cause significant morbidity. A 13-day-old neonate suffered IVC thrombosis secondary to antithrombin III deficiency, possibly contributed to by a mutation in the methyl tetrahydrofolate reductase gene. Catheter-directed thrombolysis (CDT) with recombinant tissue plasminogen activator (rt-PA, Alteplase) was used successfully to treat extensive venous thrombosis in this neonate without complications. We also review the literature on CDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Catheter-directed thrombolysis Catheter-directed thrombolysis (CDT) has been reported in 13 patients in the neonatal period (Anderson et al 1991;Aspesberro et al 1999;Dillon et al 1993;Gerling et al 2002;Khan et al 2008;Klinge et al 1998;Pritchard et al 1985;Rehan et al 1994;Ries et al 2002;Rogers et al 1989;Ryan and Andrew 1992;Wang et al 2003). In these reports, rtPA (dosage 0.01-0.1-0.5 mg/kg/h [min-median-max]) was used in 8 patients, while 4 patients received streptokinase and one was treated with urokinase.…”
Section: Interventionalmentioning
confidence: 99%
See 1 more Smart Citation
“…Catheter-directed thrombolysis Catheter-directed thrombolysis (CDT) has been reported in 13 patients in the neonatal period (Anderson et al 1991;Aspesberro et al 1999;Dillon et al 1993;Gerling et al 2002;Khan et al 2008;Klinge et al 1998;Pritchard et al 1985;Rehan et al 1994;Ries et al 2002;Rogers et al 1989;Ryan and Andrew 1992;Wang et al 2003). In these reports, rtPA (dosage 0.01-0.1-0.5 mg/kg/h [min-median-max]) was used in 8 patients, while 4 patients received streptokinase and one was treated with urokinase.…”
Section: Interventionalmentioning
confidence: 99%
“…In contrast to systemic thrombolytic therapy, effi cacy of CDT seems to be superior (82% vs 62% of complete clot lysis, 16% vs 8% partial clot lysis, 8% vs 21% failure). The safety profi le also favors CDT with a rate of one intraventricular hemorrhage (IVH) in 13 patients with CDT compared to 2 IVH, one intra abdominal bleed, one kidney rupture, one mucosal bleed and one puncture site bleed in 38 neonates with systemic thrombolysis (Khan et al 2008).…”
Section: Interventionalmentioning
confidence: 99%
“…rtPA has been effectively used to treat catheter-related intracardiac thrombus and vena cava inferior thrombus [9,10]. A study that included 20 children (age between 1 day and 16 years) with thrombosis reported that 11 patients treated with rtPA had a complete response [11].…”
Section: Discussionmentioning
confidence: 99%
“…rtPA has been effectively used to treat catheter-related intracardiac thrombus and vena cava inferior thrombus [9,10]. A study that included 20 children (aged between 1 day and 16 years) with thrombosis reported that 11 patients treated with rtPA had a complete response [11].…”
Section: Discussionmentioning
confidence: 99%